Problem Management Plus (PM+) intervention in the context of refugee psychosocial support: Research data and applications - Papathanasiou, Chrysovalantis; Pantelidou, Stella; Belekou, Pepi; Menediatou, Angeliki; Mantzari, Anastasia; Stylianidis, Stelios (Psychology: the Journal of the Hellenic Psychological Society, 2024)
The Problem Management Plus (PM+) intervention was developed by the World Health Organization to bridge the gap between mental health needs and access to quality services, as part of the WHO Mental Health Gap Action Programme (mhGAP). It is an intervention for the psychosocial support of adults who suffer from common mental health problems and face adversities in their daily lives. There is strong evidence for the intervention’s effectiveness in reducing psychological symptoms in adults exposed to adversities. Within the context of the “Community Psychosocial Workforce” program, implemented by EPAPSY (Association for Regional Development and Mental Health) in collaboration with UNHCR, the UN Refugee Agency, members of refugee communities are trained and supervised by mental health professionals to provide psychosocial support through the PM+ intervention to refugees facing emotional difficulties. The basic strategies of the intervention are based on problem-solving techniques and behavioral therapy and include anxiety management, behavioral activation, and the enhancement of social support. Additionally, symptoms of depression, anxiety, suicidality, and self-reported mental health problems are assessed using questionnaires before and after the intervention. The current article provides a detailed presentation of the intervention based on recent empirical and clinical data, as well as a presentation of its application by specially trained refugees.